KECERDASAN INTERPERSONAL DALAM AL-QUR`AN DAN URGENSINYA TERHADAP BANGUNAN PSIKOLOGI PENDIDIKAN ISLAM - Rahmatullah, Azam Sykur (STAIN Ponorogo, 2013)
Abstract; This written research and study about the verses that have close relationship with intelligence/interpersonal intelligence or humanistic social intelligence in Quran. That matter because in fact in Quran there are so many verses that showed/point out about the importance even the duty of human to have social intelligence, not only intelligence in mind (mind intelligence). Also in fact the verses that interpersonal intelligence is very needed and have active role to expand the psychology of Islamic education that have close relationship with the matter of teaching social education. So suitable/proper if this research eventually to developing deeply and wide by researcher of writer furthermore with the result the big contribution of knowledge.